Recombinant family 3 carbohydrate-binding module as a new additive for enhanced enzymatic saccharification of whole slurry from autohydrolyzed eucalyptus globulus wood - Oliveira, Carla (2018)
By-products resulting from lignocellulosics pretreatment affect the digestibility of resulting whole slurries, but this can be minimized by additives supplementation. In this work, a family 3 carbohydrate-binding module (CBM3), recombinantly produced from Escherichia coli, was used as additive in the enzymatic hydrolysis of the whole slurry from autohydrolyzed Eucalyptus globulus wood (EGW). At the higher dosage used (30 mg/gsolids), CBM3 led to an increase in glucose yield from 75 to 89%. A similar result was obtained for bovine serum albumin (BSA) (11% increase), which has a well-documented additive effect. CBM3 had no effect on the non-productive binding of enzymes, since it could not bind to EGW lignin, while it rapidly bound to cellulose, as shown by fluorescence microscopy. CBM3 is a valid additive for enhanced lignocellulosic saccharification and a valuable alternative to costly additives (e.g. polyethylene glycol) as it can be affordably produced from heterologous bacterium, thus contributing to more cost-efficient biomass valorization bioprocesses.